The Construction of Discursive Authority of Female War Survivor Portrayed in Salt to the Sea - Dianita Atika Putri; Karina Hanum Luthfia (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This paper analyzes the attainment of discursive authority of war survivors portrayed in Ruta Sepetys’ Salt to the Sea. One of the main characters, Emilia, is constructed by the narrator as a resilient young Polish woman who experiences sexual violence during World War II. However, the narrative concludes with her death in the sinking of Wilhelm Gustloff, raising questions about the limitations of female agency in war narratives. Through Susan Lanser’s feminist narratology, this study first analyzes the narrative voices employed by the war survivor. It further examines how these voices contribute to the construction of discursive authority within the novel. Furthermore, the paper explores the limitations of female discursive authority, particularly through the portrayal of Emilia’s death. Using qualitative methods, the primary data consist of narrations or utterances that represent experiences of oppression, forms of resistance, and the construction of female identity within patriarchal wartime structures. The findings reveal that Emilia’s character achieves discursive authority through personal and communal voices. However, this authority remains constrained by larger social and power structures. Emilia’s death demonstrates that obtaining voice does not necessarily guarantee complete freedom from patriarchal silencing. Therefore, this study contributes to feminist narratology by foregrounding the limitations of discursive authority in war narratives.